Retrospective Review of Carcinomatous Meningitis Management at a Tertiary Centre: Reflections on Current and Future Management. (1st October 2022) - Williams, Simon; Topping, Oliver; Sanghera, Paul; Hassan-Smith, Ghaniah
Abstract: AIMS: Carcinomatous meningitis (CM) arises following metastatic deposition of neoplastic cells in the meninges triggering a complex series of pathological changes, typically representing a terminal complication of underlying malignancy. No uniform management strategy exists for CM patients, despite research highlighting numerous treatment modalities. We present a single centre retrospective study of CM patients managed over a ten year period, along with analysis of current and future treatment modalities for CM. METHOD: Patient datasets were identified using diagnostic codes. Inclusion criteria were patients with malignant cells identified in CSF, or those with radiological features consistent with CM with a background of cancer and supporting clinical features. Data regarding patient symptomatology, management, and outcome were then gathered from electronic patient records. RESULTS: Ten cases of carcinomatous meningitis were identified. The most common primary tumour site was breast (30%). The most common presenting symptoms were headache (70%), weakness (60%), vomiting (50%), and confusion (50%). Radiological evidence of CM in the form of leptomeningeal enhancement was noted in 60% of cases. Management of CM cases was variable – six patients underwent no further anti-cancer treatment, two patients underwent chemotherapy, and two patients were planned for radiotherapy. Median length of survival from time of CM diagnosis was 30 days (IQR 15 – 63). CONCLUSION: CM patients have a poor prognosis, and significant variability exists in management. New therapeutic options are emerging, particularly in the field of targeted biologic therapies, and engagement with specialist oncology teams is recommended. Early palliative care support is essential in the management of CM patients.